One-minute and five-minute Apgar scores and child developmental health at 5 years of age: a population-based cohort study in British Columbia, Canada - Razaz, Neda (BMJ Open, 2019)
OBJECTIVES: We investigated the associations between Apgar scores at 1 and 5 min, across the entire range of score values, and child developmental health at 5 years of age. SETTING: British Columbia, Canada PARTICIPANTS: All singleton term infants without major congenital anomalies born between 1993 and 2009, who had a developmental assessment in kindergarten between 1999 and 2014. MAIN OUTCOMES AND MEASURES: Developmental vulnerability on one or more domains of the Early Development Instrument and special needs requirements. Adjusted rate ratios (aRRs) and 95% CIs were estimated using log-linear regression. RESULTS: Of the 150 081 children in the study, 45 334 (30.2%) were developmentally vulnerable and 3644 (2.5%) had special needs. There was an increasing trend in developmental vulnerability and special needs with decreasing 1 min and 5 min Apgar scores. Compared with children with an Apgar score of 10 at 5 min, the aRR for developmental vulnerability increased steadily with decreasing Apgar score from 1.02 (95% CI 1.00 to 1.04) for an Apgar score of 9 to 1.57 (95% CI 1.03 to 2.39) for an Apgar score of 2. Among children with 1 min Apgar scores in the 7–10 range, changes in Apgar scores between 1 and 5 min were associated with significant differences in developmental vulnerability. Compared with children who had an Apgar score of 9 at 1 min and 10 at 5 min, children with an Apgar score of 9 at both 1 and 5 min had higher rates of developmental vulnerability (aRR 1.03, 95% CI 1.01 to 1.05). Compared with infants with an Apgar of 10 at both 1 and 5 min, infants with a 1 min score of 10 and a 5 min score of <10 had higher rates of developmental vulnerability (aRR 1.53, 95% CI 1.08 to 2.17). CONCLUSION: Risks of adverse developmental health and having special needs at 5 years of age are inversely associated with 1 min and 5 min Apgar scores across their entire range.